Primary Malignant Melanoma of Female Urethra: A Case Report - Gadgil, Nitin M; Padmanabhan, Anitha; Palve, Meherrituja Vasant; Neelakantan, Amrita (Annals of Pathology and Laboratory Medicine, 2018)
Primary malignant melanoma of the urethra is a very rare tumor constituting 0.2% of all melanomas. Around 120 cases are published in literature till date. We report a case of malignant melanoma originating in the urethra in a postmenopausal woman which was diagnosed on biopsy and subsequent radical surgery performed.